Analysis of trust, price and service quality on purchasing decisions - wulandari, latifah (International Journal of Applied Finance and Business Studies, 2024)
The aim of this research is to analyze the influence of price, trust and service quality on purchasing decisions, as well as the influence of the three factors (price, trust, service quality) on partial or simultaneous purchasing decisions made to CV Laris Barokah customers. This research uses associative methodology. Participants in this research were all clients of CV Laris Barokah. One hundred participants met the observation sample criteria. The data collection tool used is a questionnaire, while the coefficient of determination, multiple regression, t test, and F test are the data analysis procedures. It is known that trust, price, and service quality all have positive and important influences, sometimes simultaneously.